2009
DOI: 10.1017/s0031182009990813
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofNeospora caninumin aborted bovine fetuses and dam blood samples by nested PCR and ELISA and seroprevalence in Beijing and Tianjin, China

Abstract: Neospora caninum infection is a significant cause of abortion in cattle. We investigated the tissue distribution of N. caninum in aborted bovine fetuses and dam blood samples by a nested PCR assay, and compared the nested PCR with ELISA in the diagnosis of N. caninum infection. In total, 26 aborted fetuses and 813 blood samples were collected from 8 dairy herds in Beijing (n=212) and Tianjin (n=601), China. Fifteen fetuses (57.7%) were tested N. caninum-positive by the nested PCR. N. caninum DNA was detected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
3
13
0
3
Order By: Relevance
“…Nevertheless, these results confirm the (SERRANO-MARTINEZ et al, 2007), and the results from this study have demonstrated that 38.8% (14/36) of the aborted fetuses were positive. Similar findings were described by nested PCR where 80% and 57.7% (MEDINA et al, 2006;YAO et al, 2009) of aborted fetuses were positive for N. caninum, in Mexico and China, respectively. However, other studies (PEREIRA-BUENO et al, 2003;RAZMI et al, 2006RAZMI et al, , 2010SAGER et al, 2001) have described values that ranged from 11.9 to 33%.…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, these results confirm the (SERRANO-MARTINEZ et al, 2007), and the results from this study have demonstrated that 38.8% (14/36) of the aborted fetuses were positive. Similar findings were described by nested PCR where 80% and 57.7% (MEDINA et al, 2006;YAO et al, 2009) of aborted fetuses were positive for N. caninum, in Mexico and China, respectively. However, other studies (PEREIRA-BUENO et al, 2003;RAZMI et al, 2006RAZMI et al, , 2010SAGER et al, 2001) have described values that ranged from 11.9 to 33%.…”
Section: Discussionsupporting
confidence: 83%
“…Fluctuations in the results similar to these have previously been described (McINNES et al, 2006;DIJKSTRA et al, 2008;MORÉ et al, 2009;YAO et al, 2009;MARQUES et al, 2011). McInnes et al (2006) reported that there was no correlation between the serological tests on dams and the PCR on their fetuses, and a high percentage of infected fetuses had serologically negative dams.…”
Section: Discussionsupporting
confidence: 72%
“…A neosporose é uma doença causada pelo N. caninum, parasito intracelular obrigatório formador de cistos, que pode infectar uma série de hospedeiros de interesse produtivo, como os ruminantes (YAO et al, 2009). …”
Section: Agente Etiológicounclassified